Learning English as A Foreign Language (EFL): A Narratology - Abigail B. Quimosing (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
This study aimed at narrating the lived experiences of a Taiwanese student in learning English as a foreign language, which includes identifying the other means of learning English as a foreign language, the difficulties encountered in learning English as a foreign language and means of overcoming such. This study made use of a qualitative research design, employing a narrative approach, wherein the data were gathered through face-to-face interviews with the participant – a student representative who had been learning English at school since 13. The interview was audiotaped and transcribed, re-transcribed, and re-storied. The study found that other than in formal school, English could be learned through English tutorial classes, reading materials such as books, journals, and magazines in English, making use of internet applications with English as a medium such as Google, Facebook, Yahoo, Instagram, and talk or chat to foreigners. The study also revealed that the learner encountered difficulties in grammar and pronunciations. As observed, the student was not able to communicate in English effectively – with many grammar lapses and mispronunciations. It was further revealed that motivation and constant practice in English communication is seen by the learner as means of overcoming such difficulties. In conclusion, the study drew that foreign language learning is more difficult because exposure to the language is so limited. However, giving more talks to students in the classroom will provide means for students to practice English as a foreign language, as well as exposure to different internet applications with English as a medium.